The 2030 Agenda from the perspective of the peripheries: limits and impostures of the 17 Sustainable Development Goals - de Oliveira, Leandro Dias (Geografares, 2024)
The objective of this article is to evaluate, from a critical perspective and from the perspective of the peripheries, the geopolitical and ideological role of the 17 Sustainable Development Goals. In order to fulfill this aim, a geopolitical review of the main events that culminated in the publication of the document Transforming Our World: The 2030 Agenda for Sustainable Development (UN, 2015). Finally, by evaluating reports from the Sustainable Development Solutions Network (SDSN), it was possible to make some considerations about the real prospects for achieving the 17 SDGs, especially in the world’s peripheries.